A study of the nature of the oxidant in V2O5-MoO3/Al2O3 catalyst - Taufiq-Yap, Y.H.; Waugh, K.C. (Elsevier BV, 2001)
The nature of the oxidising species in/on a V2O5-MoO3/ Al2O3 catalyst has been studied by using the combination of transient kinetic techniques (i) oxygen temperature programmed desorption (TPD), (ii) temperature programmed reduction (TPR) and (iii) temperature programmed oxidation (TPO). The oxygen TPD spectrum observed two molecular oxygen species having desorption peak maxima of 774 and 825 K. Three peak maxima (705, 915 and 1120 K) were observed in the rate of anaerobic oxidation of CO indicating that three types of kinetically different oxygen states exist in the catalyst. Re-oxidation of CO reduced the material by N2O and resulted in the replacement of the lattice oxygen by N2O, the re-oxidation occurring at 683; 798 and 918 K, but does not reproduce the original morphology of the catalyst.